2009
DOI: 10.1029/2008ja013687
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of coronal type III solar radio bursts: 3. Effects of beam and coronal parameters

Abstract: [1] A recently developed simulation model is used to investigate the effects of varying the coronal and electron heating conditions on the dynamic spectra of coronal type III bursts (70-370 MHz) observed at Earth. The flux of 2f p emission is significantly higher than that of f p emission, which is unlikely to be observable except under very favorable propagation conditions. Moreover, the 2f p emission is unlikely to continue into the solar wind, although some bursts are very strong and will extend into the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 73 publications
6
35
0
Order By: Relevance
“…magnetic connectivity), so we do not expect all beams with a large electron flux above 25 keV to produce interplanetary type III bursts. The increase in type III flux when the number of electrons above 25 keV is increased was demonstrated numerically by Li et al (2008aLi et al ( , 2009Li et al ( , 2011) using a hot, propagating Maxwellian. They showed that increasing the temperature of the initial Maxwellian beam increases the type III radio flux and increases the bandwidth; the burst starts at higher frequencies and stops at lower frequencies.…”
Section: Interplanetary Bursts and >25 Kev Electronsmentioning
confidence: 99%
See 1 more Smart Citation
“…magnetic connectivity), so we do not expect all beams with a large electron flux above 25 keV to produce interplanetary type III bursts. The increase in type III flux when the number of electrons above 25 keV is increased was demonstrated numerically by Li et al (2008aLi et al ( , 2009Li et al ( , 2011) using a hot, propagating Maxwellian. They showed that increasing the temperature of the initial Maxwellian beam increases the type III radio flux and increases the bandwidth; the burst starts at higher frequencies and stops at lower frequencies.…”
Section: Interplanetary Bursts and >25 Kev Electronsmentioning
confidence: 99%
“…In recent years, several numerical simulations have been performed to simulate the radio coronal type III emissions from energetic electrons and investigate the effects of beam and coronal parameters on the emission (e.g. Li et al 2008bLi et al , 2009Li et al , 2011Tsiklauri 2011;Li & Cairns 2014;Ratcliffe et al 2014) Since the discovery of type III bursts and the advent of continuous and regular HXR observations, many studies have analysed the relationship between type III bursts and hard X-ray emissions. The first studies of the temporal correlations between metric (coronal) type III bursts and HXRs above 10 keV were achieved by Kane (1972Kane ( , 1981.…”
Section: Introductionmentioning
confidence: 99%
“…The series of papers by Li et al (2008aLi et al ( ,b, 2009 were the first to trace an electron beam from the injection site into the corona and solar wind, and calculate the resulting radio emission fully numerically, rather than by analytical estimates. These simulations have more recently been extended to cover a wider frequency range, and used to explore the effects of the background plasma on the emission.…”
Section: "State Of the Art" Simulationsmentioning
confidence: 99%
“…Assuming a type-IIIlike emission mechanism for the small-scale features observed in the MWA data, we arrive at a one-to-one correspondence between their peak frequencies and the electron densities at their heights of production in the solar corona. We assume a 4× Newkirk (1961) density profile in the solar corona in order to translate from electron densities (Li et al 2009) into heights (h) in the solar corona. Having computed ν start , Δν and Δt for every feature, we can also determine a height band (Δh) and a propagation speed (v = Δh/Δt)for every feature.…”
Section: Comparison With Type-iii Burstsmentioning
confidence: 99%